2019
DOI: 10.1007/s10661-019-7925-y
|View full text |Cite
|
Sign up to set email alerts
|

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill

Abstract: The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican (Pelecanus erythrorhynchos), common loon (Gavia immer), and northern gannet (Morus bassanus). Point counts (pelican, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several contributing factors have been attributed to mortality in common loons in marine environments including emaciation, food limitation, net entanglement, oiling associated with spills, contaminants, biotoxin exposure (e.g. botulism, ‘red tide'), parasitic infection, fungal infection and trauma (Alexander 1991, Spitzer 1995, Forrester et al 1997, Daoust et al 1998, Sidor et al 2003, Benjamins et al 2008, Starr et al 2017, Paruk et al 2019). Parasitic infection was the most prevalent contributing cause of mortality identified among juvenile loon carcasses recovered in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several contributing factors have been attributed to mortality in common loons in marine environments including emaciation, food limitation, net entanglement, oiling associated with spills, contaminants, biotoxin exposure (e.g. botulism, ‘red tide'), parasitic infection, fungal infection and trauma (Alexander 1991, Spitzer 1995, Forrester et al 1997, Daoust et al 1998, Sidor et al 2003, Benjamins et al 2008, Starr et al 2017, Paruk et al 2019). Parasitic infection was the most prevalent contributing cause of mortality identified among juvenile loon carcasses recovered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Potential exposure of loons to petroleum or oil dispersants either directly or via prey ingestion is of concern, as these contaminants could possibly have negative effects on the productivity of affected birds. Paruk et al (2019) reported evidence of oiling among 23.6% of 1148 common loons examined in the GOM in the first winter following the 2010 Deepwater Horizon oil spill, and estimated mortality at 10.7% (based on the degree of oiling) among the loons assessed. Petroleum oil exposure has been linked to increased stress and reduced breeding success through altered breeding behavior and impaired egg formation and laying in birds (Fry 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Later in the laboratory, bodies and wing feathers were inspected visually for oil contamination as reflected by the feathers being sticky with a wet and shiny appearance rather than smooth and dry. Visual inspection of the plumage has been used to assess whether birds are contaminated with oil (Joensen, 1972 ; Paruk et al., 2019 ). The method has been recommended or used by the Trilateral Monitoring and Assessment Program for the Wadden Sea, by OSPAR, the Oslo‐Paris Commission, by US Wildlife Service and in Greenland in monitoring programs of oiled seabirds washed ashore (Berg, 2005 ; Camphuysen, 2005 ; Schulz et al., 2017 ; Wegeberg et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Haney et al (2017) noted the application of UV fluorescence to detect trace oiling of in-hand birds during the Deepwater Horizon. Paruk et al (2019) used digital photographs to categorize the degree of oiling for three species (Common Loons, American White Pelicans [Pelecanus erythrorhynchos], and Northern Gannets) post Deepwater Horizon and extrapolated impacts to populations.…”
Section: Detection Of Lightly Oiled Birdsmentioning
confidence: 99%